Identification of School System Approaches at MAS Al-Washliyah 22 Tembung - Marsyela; Marsyeli; Uswatun Hasanah; Wardatun Thaibah Marpaung; Sifa Maulida (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
In this research, we conducted an in-depth analysis of the various systems approaches implemented at the MAS Al-Washliyah Tembung school to improve the quality of education. We identified various aspects of the systems approach, starting from the application of the systems approach in education at the school, the obstacles in explaining the systems approach, elements or components in education, what approaches are used in the learning process and the stages in implementing the systems approach. The systems approach in schools can include analysis of various systems approaches applied in the educational environment. This can include learning approaches, school management, and curriculum development. Through this research, we hope to provide deeper insight into the systems approach that exists at the MAS Alwashliyah 22 Tembung school in the context of school education.